Adenoid cystic carcinoma of the breast – an uncommon malignancy with unpredictable clinical behaviour. A case series of three patients - Sołek, Julia M.; Braun, Marcin; Kalwas, Marta; Jesionek-Kupnicka, Dorota; Romańska, Hanna (Contemporary Oncology/Współczesna Onkologia, 2020)
Adenoid cystic carcinoma (AdCC) is a common tumour of the minor salivary gland, rarely seen in other anatomical locations. In particular, AdCC of the breast accounts for < 0.1% of patients diagnosed with breast cancer. Here we report our institutional experience with three cases of breast AdCC diagnosed between 2009 and 2017. Mean age of women included in the report was 53 (range from 41 to 62). One case was of no special subtype, two were solid variants and one presented with a component of invasive ductal carcinoma. At diagnosis in all cases neither lymph node involvement nor distal metastases were detected. All patients underwent surgical resection of the tumour – mastectomy or lumpectomy, followed by either adjuvant radiotherapy and chemotherapy (one case), chemotherapy without radiotherapy (one case) or no treatment (one case). Two patients were reported to develop metastatic disease. No deaths were recorded. In contrast to other anatomical locations AdCC of the breast is regarded as a rare tumour with low malignant potential. However, as shown in our case series, it can present as an aggressive disease with distal metastases, which calls for deep awareness among both pathologists and clinicians involved in the process of diagnosis and therapy.